2022
DOI: 10.3390/ijms23052610
|View full text |Cite
|
Sign up to set email alerts
|

CuxCo1-xFe2O4 (x = 0.33, 0.67, 1) Spinel Ferrite Nanoparticles Based Thermoplastic Polyurethane Nanocomposites with Reduced Graphene Oxide for Highly Efficient Electromagnetic Interference Shielding

Abstract: CuxCo1−xFe2O4 (x = 0.33, 0.67, 1)-reduced graphene oxide (rGO)-thermoplastic polyurethane (TPU) nanocomposites exhibiting highly efficient electromagnetic interference (EMI) shielding were prepared by a melt-mixing approach using a microcompounder. Spinel ferrite Cu0.33Co0.67Fe2O4 (CuCoF1), Cu0.67Co0.33Fe2O4 (CuCoF2) and CuFe2O4 (CuF3) nanoparticles were synthesized using the sonochemical method. The CuCoF1 and CuCoF2 exhibited typical ferromagnetic features, whereas CuF3 displayed superparamagnetic characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 103 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…Thus, it is possible through the modification of the particle surface and thereby affecting the frequency characteristics of permeability and permittivity of MREs to tune the operating frequency range of SE, making possible their application in the frequency range from nearly 700 MHz to 1.6 GHz, in which many communication and information transmission systems usually operate [ 9 ]. The values presented in this study are very promising and still competitive to the state of the art as reported by Anju et al combining magnetic nanoparticles, reduced graphene oxide in TPU matrix with shielding efficiency on transmission of 58.8 dB for a sample thickness 1 mm [ 45 ]. Utilization of the magnetite particles with reduced graphene oxide provides the reflection of 25 dB with a sample thickness of 1 mm [ 46 ].…”
Section: Resultsmentioning
confidence: 63%
“…Thus, it is possible through the modification of the particle surface and thereby affecting the frequency characteristics of permeability and permittivity of MREs to tune the operating frequency range of SE, making possible their application in the frequency range from nearly 700 MHz to 1.6 GHz, in which many communication and information transmission systems usually operate [ 9 ]. The values presented in this study are very promising and still competitive to the state of the art as reported by Anju et al combining magnetic nanoparticles, reduced graphene oxide in TPU matrix with shielding efficiency on transmission of 58.8 dB for a sample thickness 1 mm [ 45 ]. Utilization of the magnetite particles with reduced graphene oxide provides the reflection of 25 dB with a sample thickness of 1 mm [ 46 ].…”
Section: Resultsmentioning
confidence: 63%
“…The real part of permittivity ε ′ and permeability μ ′ signifies the ability to store electromagnetic energy, whereas the imaginary part of permittivity ε ′′ and permeability μ ′′ corresponds to the attenuation ability of electromagnetic energy. 62 …”
Section: Resultsmentioning
confidence: 99%
“…The real part of permittivity 3 0 and permeability m 0 signies the ability to store electromagnetic energy, whereas the imaginary part of permittivity 3 00 and permeability m 00 corresponds to the attenuation ability of electromagnetic energy. 62 Fig. 9(a) illustrates the variation of the real part of the permittivity 3 0 as a function of the frequency.…”
Section: Papermentioning
confidence: 99%
“…Spinel ferrites (MFe 2 O 4 ) have diverse properties that make them attractive for various applications. They possess excellent magnetic properties, making them essential in magnetic devices like recording devices, data storage, sensors, and electromagnetic interference shielding 1 3 . Spinel ferrites are known for their exceptional electrical conductivity and dielectric properties.…”
Section: Introductionmentioning
confidence: 99%